Synthesis of Crude Palm Oil-Based Polyol Ester as Biolubricant (Universitas Negeri Semarang, 2021)
The decline in crude oil reserves as a raw material for the manufacture of lubricants and the need to reduce pollution from mineral lubricants has begun to encourage the use of waste and pollution reduction technologies to reduce environmental problems. One realization is an alternative lubricant called biolubricant. Biolubricant is considered rapidly biodegradable, non-toxic, and thought to pose less or no risk to the environment and its users compared to petroleum-based lubricants. This study aimed to produce polyol esters as biolubricant through the acetylation reaction of polyols from crude palm oil (CPO) and to investigate the physical and chemical properties of the resulting polyol esters. From the study results, the kinematic viscosity of 40 °C in the resulting polyol ester was 46.2339 cSt, while the kinematic viscosity at 100 °C was 8.7417 cSt. The viscosity index and flash point of polyol ester obtained were 144.0818 and 282.3 °C. The highest conversion of 38.41% polyol ester production was achieved at 80 °C for 35 minutes using a 3% wt/wt catalyst. This study shows that palm oil esters have great potential to obtain lubricants with high biodegradability and better physicochemical properties.